Endocrine activity of mycotoxins and mycotoxin mixtures. (October 2016) - Demaegdt, Heidi; Daminet, Britt; Evrard, Annick; Scippo, Marie-Louise; Muller, Marc; Pussemier, Luc; Callebaut, Alfons; Vandermeiren, Karine
Abstract: Reporter gene assays incorporating nuclear receptors (estrogen, androgen, thyroid β and PPARγ2) have been implemented to assess the endocrine activity of 13 mycotoxins and their mixtures. As expected, zearalenone and its metabolites α-zearalenol and β- zearalenol turned out to have the strongest estrogenic potency (EC50 8, 7 10-10 ± 0, 8; 3, 1 10-11 ± 0, 5 and 1, 3 10-8 ± 0, 3 M respectively). The metabolite of deoxynivalenol, 3-acetyl-deoxynivalenol also had estrogenic activity (EC50 3, 8 10-7 ± 1, 1 M). Furthermore, most of the mycotoxins (and their mixtures) showed anti-androgenic effects (15-acetyldeoxynivalenol, 3-acetyl-deoxynivalenol and α-zearalenol with potencies within one order of magnitude of that of the reference compound flutamide). In particular, deoxynivalenol and 15-acetyl-deoxynivalenol acted as antagonists for the PPARy2 receptor. When testing mixtures of mycotoxins on the same cell systems, we showed that most of the mixtures reacted as predicted by the concentration addition (CA) theory. Generally, the CA was within the 95% confidence interval of the observed ones, only minor deviations were detected. Although these reporter gene tests cannot be directly extrapolated in vivo, they can be the basis for further research. Especially the additive effects of ZEN and its metabolites are of importance and could have repercussions in vivo . Highlights: Reporter gene assays assessed the endocrine activity of 13 mycotoxins and mixtures. Like ZEN and metabolites, 3-acetylDON showed ER activity (EC50 3.8 10 −7  ± 1.1 M). Most of the mycotoxins (and their mixtures) showed anti-androgenic effects. DON and 15-acetylDON acted as antagonists for PPARy2. Most mixtures reacted as predicted by the concentration addition (CA) theory.